1993
DOI: 10.1084/jem.177.6.1815
|View full text |Cite
|
Sign up to set email alerts
|

Tumor necrosis factor alpha cooperates with interleukin 3 in the recruitment of a primitive subset of human CD34+ progenitors.

Abstract: SummaryWe have recently demonstrated that tumor necrosis factor ol (TNF-ot) potentiates interleukin 3 (IL-3)-and granulocyte/macrophage colony-stimulating factor-induced growth of CD34 + hematopoietic progenitor cells (HPC), and favors the generation of dendritic/Langerhans cells. The stimulatory effect of TNF-ot was detailed in the present study. Thus, CD34 + HPC entering in cycle (S/G2M) after a 48-h pulse with IL-3 expressed the transferrin receptor (TfR), and fluorescence-activated cell sorter-separated Tf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

1995
1995
2013
2013

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 46 publications
(20 citation statements)
references
References 24 publications
0
20
0
Order By: Relevance
“…IL-3 has been described as a myeloid growth factor (Ihle, 1992). Comparing the generation of DC from human CD34 pos cord blood cells in vitro, IL-3 is similarly potent in raising human myeloid DC when compared with GM-CSF (Caux et al, 1993). Human and murine thymic DC precursor cells seem to be especially unresponsive to GM-CSF but readily expand in culture with a cytokine cocktail containing IL-3 (Kelly et al, 2001;Saunders et al, 1996), possibly indicating that IL-3 but not GM-CSF is required for thymic DC progeny in vivo.…”
Section: The Neglected: Il-3mentioning
confidence: 96%
“…IL-3 has been described as a myeloid growth factor (Ihle, 1992). Comparing the generation of DC from human CD34 pos cord blood cells in vitro, IL-3 is similarly potent in raising human myeloid DC when compared with GM-CSF (Caux et al, 1993). Human and murine thymic DC precursor cells seem to be especially unresponsive to GM-CSF but readily expand in culture with a cytokine cocktail containing IL-3 (Kelly et al, 2001;Saunders et al, 1996), possibly indicating that IL-3 but not GM-CSF is required for thymic DC progeny in vivo.…”
Section: The Neglected: Il-3mentioning
confidence: 96%
“…This has been demonstrated with regard to BM-derived Langerhans cells, 23 and for the development of DCs from early progenitor-stage cells. 24 Moreover, that effect may be the consequence of TNF-␣-mediated up-regulation of GM-CSF receptors on DC precursors. 25 Other studies have demonstrated that TNF-␣ plus IL-3 in the absence of GM-CSF can mediate DC development from human cord blood, 26 implying that TNF-␣ can act synergistically with several growth-promoting factors, or possibly that it induces the secretion of other growth-promoting factors, but nonetheless further defining an important role for TNF-␣ in the process of DC development within primary hematopoietic tissues.…”
Section: Discussionmentioning
confidence: 99%
“…rhGM-CSF (specific activity: 2 • 10 a U/rag; Schering-Plough Research Institute, Kenilworth, NJ) was used at a saturating concentration of 100 ng/ml (200 U/ml). rhTNFct (specific activity: 2 • 107 U/rag; Genzyme, Boston, MA) was used at an optimal concentration of 2.5 ng/ml (50 U/ml) (20) rhSCF (specific activity 4 • 105 U/mg; R&D, Abington, UK) and rhM-CSF (specific activity: 2 • 106 U/mg; R&D) were used at optimal concentrations of 25 ng/ml. Umbil-ical cord blood samples were obtained according to institutional guidelines.…”
Section: Methodsmentioning
confidence: 99%